Bank Financial Institutions in Indonesia and Their Supervision - Y Yudanto; Wardah Yuspin (Proceeding International Conference Restructuring and Transforming Law, 2022)
Almost all financial activities of people around the world cannot be separated from the role of financial institutions. This institution is the financial intermediary for the community, namely those who need funds and those who provide funds. Apart from acting as an intermediary, this institution also plays a major role in maintaining the stability of money circulation and the country's economy. Financial institutions in Indonesia are divided into two types, namely Bank Financial Institutions and Non-Bank Financial Institutions, both of which have important roles in the community's economic activities. This Financial Institution in carrying out its role requires supervision, which is intended so that the Financial Institution can continue to run according to its corridor. Furthermore, in this article, the author will specifically try to discuss about Bank Financial Institutions and their supervision, both before the birth of the OJK and after the birth of the OJK. The research method that the author uses is a normative research method, byread or analyze written materials or library materials, while the type of approach used in this paper is the statutory approach and the legal concept analysis approach.